Administration of Intravenous Dexmedetomidine and Acetaminophen for Improved Postoperative Pain Management in Primary Palatoplasty. Issue 2 (2nd March 2022) - Ichiuji, Brynne; Mantilla-Rivas, Esperanza; Rana, Md Sohel; Mamidi, Ishwarya; Manrique, Monica; Stein, Jason; Aivaz, Marudeen; McGrath, Jennifer; Rogers, Gary F.; Oh, Albert K.
Abstract : Objective: Suboptimal pain management after primary palatoplasty (PP) may lead to complications such as hypoxemia, and increased hospital length of stay. Opioids are the first option for postoperative acute pain control after PP; however, adverse effects include excessive sedation, respiratory depression, and death, among others. Thus, optimizing postoperative pain control using opioid-sparing techniques is critically important. This paper aims to analyze efficacy and safety of combined intravenous (IV), dexmedetomidine, and IV acetaminophen during PP. Methods: Review of a cohort of patients who underwent PP from April 2009 to July 2018 at a large free-standing children's hospital was performed, comparing patients who received combined IV dexmedetomidine and acetaminophen with those who did not receive either of the 2 medications. Efficacy was measured through opioid and nonopioid analgesic dose and timing, pain scores, duration to oral intake, and length of stay. Safety was measured by 30-day complication rates including readmission for bleeding and need for supplementary oxygen. Results: Total postoperative acetaminophen ( P = 0.01) and recovery room fentanyl ( P < 0.001) requirements were significantly lower in the study group compared with the control group. Length of stay, oral intake duration, pain scores, total postoperative opioid requirements, and complications rates trended favorably in the study group, though differences did not reach statistical significance. Conclusions: Intraoperative IV dexmedetomidine and acetaminophen during PP provides safe and effective perioperative pain control, resulting in statistically significant decreased need for postoperative acetaminophen and fentanyl. Larger studies are necessary to determine if other trends identified in this study may be significant.